The Relationship Between Timeliness of Food Distribution and Food Temperature with Lunch Leftovers from Regular Food Diet Patients at Regional General Hospitals - Sekar Kusumawati Kusumawati (Poltekkes Kemenkes Mataram, 2024)
Background: Leftover food is food left by respondents on their eating plates. Leftovers can be categorized as good if the patient can finish food > 80%, so the patient does not leave food > 20%. The timeliness of food distribution and temperature can affect food waste in the hospital.Research Methods: This research aimed to determine the relationship between the timeliness of food distribution and food temperature with the respondents' leftover lunch. The research design was an analytical quantitative observational with a cross-sectional approach, carried out in May 2023 at the Inner Mangunang Tanggamus General Hospital. The research sample was all class III inpatients with a regular diet of 30 respondents. Bivariate analysis in this study used the Chi-Square test.Research Result: The results showed a relationship between the timeliness of food distribution and food waste (p=0.007) and between food temperature and food waste (p=0.016).Conclusion: Based on the research results, it can be concluded that there is a relationship between the timeliness of food distribution and food temperature with the remaining lunch of the respondents